(untitled) (Jurnal Bina Praja, 2016)
Despite being regulated by the Presidential Decree No 25 of 2008, which then was simplified by the Law No 24 of 2013, the registration of birth and death in Indonesia does not automatically promote the scope of birth and death certificate in Indonesia. Local governments are with their respective innovations on these issue, yet these inovations tend to add more bureaucracy and create new problems. The purpose of this study is to examine how the real practice of birth and death registration, as well as to identify the problems, implications, and the causes of the registration implementation. This study was conducted in 2015 in two districts and two municipalities in Banten and West Java Provinces using descriptive research method and descriptive-qualitative analysis. This study found that birth and death registration are still referring to the Presidential Decree No 25 of 2008 which implementation is still adapting the “convenience” of the Law No 24 of 2013. The implementation of birth and death registration still experiences many obstacles, such as: the lack of death reporting by the head of neighborhood (RT); applicants still experience tiered bureaucracy that leads to a lengthy process of completing the document, limited access in the district area, and time service mismatch; human resources in the ub-district/village that are not adequately supportive to the civil registration services; and documentation process in the implementing agencies still relies on manual systems.